Adipose-Derived Stem Cells Therapy for Radiation-Induced Skin Injury. Issue 6 (1st December 2021) - Huayllani, Maria T.; Ruiz-Garcia, Henry; Boczar, Daniel; Avila, Francisco R.; Lu, Xiaona; Rinker, Brian D.; Moran, Steven L.; Sarabia-Estrada, Rachel; Quiñones-Hinojosa, Alfredo; Forte, Antonio J.
Abstract : Background: Radiation-induced skin injuries have been treated with different medical therapies and have shown diverse outcomes. We aim to evaluate the effect of adipose-derived stem cells (ADSCs) therapy on radiation-induced skin injury. Methods: We performed a review by querying PubMed, Ovid MEDLINE, and EMBASE databases from inception to April 2020 following Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines. The MeSH terms "adipose-derived stem cells, " "wound healing, " "radiation, " and synonyms in combinations determined our search strategy. Experimental peer-reviewed articles describing the protocol and comparing the results with controls were included. Non-English studies were excluded. Results: Our search recorded a total of 137 articles. Only 8 studies met our inclusion criteria and were included in this review. Five studies evaluated the use of ADSC alone, whereas the others evaluated the efficacy of ADSC seeded in scaffolds. Adipose-derived stem cell–based therapies, either alone or seeded in scaffolds, were shown to improve wound healing in most studies when compared with controls. Conclusions: There is evidence supporting the positive benefits from ADSC-based therapies in radiation-induced skin injury. However, further studies are needed to standardize the method of ADSC extraction, radiation-induced skin injury experimental model, and increase the time of follow-up to evaluate the results accurately.